In vitro antibacterial activity of vernonia amygdalina leaves extracts against pathogen of pineapple heart rot disease - Abdul Aziz, Noorshilawati; Mazlan, Hamimah; Abdullah, Nur Suraya; Omar, Muhammad Nor (UPENA Universiti Teknologi MARA Cawangan Pahang, 2018)
Heart rot disease is one of the major diseases in pineapple cultivation in Malaysia. Josapine and N36 are among varieties that vulnerable to the heart rot disease. The infection can reduce up to 50% yield. In vitro antibacterial activity of four Vernonia amygdalina leaves extract (hexane, chloroform, methanol and aqueous) was carried out and evaluated against pathogen of pineapple heart rot disease. The antibacterial activity was evaluated using well diffusion method where three concentrations for each extract were prepared. The results revealed V. amygdalina chloroform and aqueous leaves extracts at 10000 ppm shows greater inhibition zone than positive control. V. amygdalina hexane leaves extracts, however, did not shows any inhibition zone at any concentrations. Meanwhile, the V. amygdalina methanol leaves extract shows antibacterial activity against the pathogen of pineapple heart rot disease but not as good as positive control. Phytochemical screening was also carried out to determine the presence of alkaloid, flavanoid, glycoside, phenol, saponin, steroid, and tannins as these compounds may attribute to the result. The screening revealed that both V. amygdalina chloroform and aqueous leaves extracts contain alkaloid, saponin, and tannin. Result shows the potentials of V. amygdalina as an antibacterial agent in combating pineapple heart rot disease.